ENGLISH AS A MEDIUM OF INSTRUCTION IN EFL CLASS: A STORY FROM TWO EFL TEACHERS IN A RURAL AREA IN PESANTREN IN EAST JAVA - Inayatus Sholichah; Dewi Nurul Qomariyah; Khoiriyah; Moch. Imam Machfudi (English Review: Journal of English Education, 2025)
Numerous academics have advocated using English as a medium of instruction (EMI). However, little focus has been placed on how an EFL teacher used EMI in a rural area in Pesantren in East Java. This study details the usage of EMI in EFL classes with students of various ethnic backgrounds, in particular. This study employs a narrative inquiry to examine two teachers' experiences teaching English as a second language over their roughly 16 years in senior high schools and teachers who spend approximately four years teaching English in the pesantren. The information was gleaned from a narrative mediated by a voice note and video call. Thematic analysis was used to examine the data. The findings indicate that there are two aspects to using EMI in EFL classes: (1) looking back, (2) looking both internally and externally, and (3) looking forward. The study's implementation is that the teacher's pedagogical expertise and language ability become the primary supports in EMI classes.